A Rose Blooms in the Winter: The Tradition of the Hortus Conclusus and its Significance as a Devotional Emblem. (December 2013) - Larson, Victoria
Abstract The hortus conclusus, or the "garden enclosed, " is a motif of biblical origin that images the Virgin Mary as a cloistered garden. Gaining popularity in the early medieval period, the Marian hortus conclusus remained the property of the Catholic church after the Reformation. There it briefly thrived, reaching its apogee in the early modern period as the eponymous subject of Henry Hawkins' emblem book, Partheneia Sacra. The Virgin in (and as) the garden still lives a half‐life today, continuing to appear without our recognizing it in medieval and Renaissance artwork, in hymns, in the names of flowers, and in prayers. Where it is known, the Marian hortus conclusus is usually perceived as a Catholic object of adoration, but its enduring nature suggests that it holds promise as a catholic subject of devotion as well.